First recourse for care-seeking and associated factors among rural populations in the eastern Democratic Republic of the Congo - Wyvine Ansima Bapolisi; Hermès Karemere; Freddy Ndogozi; Aimé Cikomola; Ghislain Kasongo; Albert Ntambwe; Ghislain Bisimwa (BMC, 2021)
Abstract Background Access to quality healthcare is a global fundamental human right. However, in the Democratic Republic of the Congo, several parameters affect the choices of health service users in fragile, rural contexts (zones). The overarching aim of this study was to identify the first recourse of healthcare-seeking and the determinants of utilization of health centers (primary health care structures) in the rural health zones of Katana and Walungu. Methods A cross-sectional survey was conducted from June to September 2017. Consenting respondents comprised 1751 adults. Continuous data were summarized using means (standard deviation) and medians (interquartile range). We used Pearson's chi-square test and Fisher exact test to compare proportions. Logistic regression was run to assess socio-determinants of health center utilization. Results The morbidity rate of the sample population for the previous month was 86.4% (n = 1501) of which 60% used health centers for their last morbid episode and 20% did not. 5.3% of the respondents patronized prayer rooms and 7.9% resorted to self-medication principally because the cost was low, or the services were fast. Being female (OR: 1.51; p = 0.005) and a higher level of education (OR: 1.79; p = 0.032) were determinants of the use of health centers in Walungu. Only the level of education was associated with the use of health centers in Katana (OR: 2.78; p = 0.045). Conclusion Our findings suggest that health centers are the first recourse for the majority of the population during an illness. However, a significant percentage of patients are still using traditional healers or prayer rooms because the cost is low. Our results suggest that future interventions to encourage integrated health service use should target those with lower levels of education.